Antimicrobial properties of prunin, a citric flavanone glucoside, and its prunin 6″-O-lauroyl ester - Celiz, Gustavo (2010)
Aims: To determine the antimicrobial potential of prunin (P), a flavanone glucoside resulting from the hydrolysis of naringin present in grapefruit, and of its prunin 6″-O-lauroyl ester (PL), synthesized by enzymatic catalysis. Methods and Results: P and its lauroyl ester were tested against Gram-negative and Gram-positive bacteria, yeasts and moulds. P showed no inhibitory effect against the micro-organisms assayed, but stimulated growth of Pseudomonas aeruginosa and different Bacilllus sp. However, 150 g ml-1 of PL inhibited Escherichia coli, Salmonella enterica serovar Enteritidis, Salmonella enterica serovar Typhimurium, many Bacillus sp., Staphylococcus aureus ATCC29213, Enterococcus avium DSMZ17511, and different Listeria monocytogenes strains. In the last case, L. monocytogenes, sensitive or bacteriocin-resistant cells, lost nearly 4-log reductions after 30 min of contact. A bactericidal mode of action was determined using both scanning and transmission electronic microscopies. Conclusions: PL could be used as a food additive, because at low concentration (150 g ml-1) it exhibited antimicrobial activity against important food-borne pathogens. A bactericidal effect was also determined on L. monocytogenes sensitive and bacteriocin-resistant mutant strains. P did not show any antimicrobial property at all. Significance and Impact of the Study: PL is a potential antimicrobial compound with a high anti-Listeria property. © 2010 The Society for Applied Microbiology.